The missed Constitutional Reform and its possible impact on the sustainability of the Italian National Health Service - Signorelli, Carlo; Oddone, Anna; Gozzini, Armando; Petrelli, Fabio; Tirani, Marcello; Zangrandi, Antonello; Zoni, Roberta; Florindo, Nicola (Acta Biomedica Atenei Parmensis, 2017)
The rejection of the Constitutional Law Bill No.1429-D in the December 2016 referendum, has stimulated a cause for reflection on current health legislation and the future prospects of the Italian National Health Service; also in the context of the recent approval of the new Essential Levels of care (LEA) and other relevant laws approved by the Parliament. This article analyzes possible future legislative and organizational scenarios with particular regard to issues related to National health system’s sustainability.